(untitled) (Comparative Professional Pedagogy, 2025)
This article presents a comparative analysis of the structure of undergraduate programmes for coach-educator training at the leading UK universities in the context of their alignment with contemporary requirements of the sports industry. In the modern world, where sports science is rapidly evolving, the demand for highly qualified specialists in sports coaching and physical education is increasing, necessitating the adaptation of educational programmes to the rapidly changing needs of the sports industry. The article examines the main aspects of educational process organisation at ten leading universities, particularly the structure of curricula, teaching methods for pedagogical disciplines, approaches to evaluating coaching-pedagogical competencies, and the role of mandatory placements in schools and educational institutions. Special attention is given to the connection between these programmes and physical education teacher training standards, professional accreditations from CIMSPA and UK Coaching, as well as qualification requirements for employment in educational institutions. Based on comparative analysis, key elements influencing the quality of future coach-educator training have been identified: development of pedagogical competencies for teaching sports disciplines, integration of coaching and educational methodologies, programme orientation towards dual training for working with both athletes and students in educational institutions, and close collaboration with schools and teacher training colleges. The article emphasises the importance of innovative components in educational programmes, such as integration of pedagogical practices with coaching methodologies, placements in schools and educational institutions, collaboration with education faculties, and development of skills for teaching sports disciplines to different age groups. It is established that programmes oriented towards dual training (coach + educator) and collaboration with both professional sports organisations and educational institutions enhance the versatility and competitiveness of graduates in the labour market.